Analisis Pengaruh Promosi, Kualitas, Pelayanan Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian (Studi Pada Konsumen E-Commerse Bukalapak) - najma lazwarda (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
ABSTRACT: The background in this problem is the decrease in the number of consumers on e-commerce Bukalapak consecutively from year to year. So the formulation in this study is how to increase the level of purchasing decisions on BukaLapak e-commers consumers. This study aims to determine the effect of promotion, service quality, and electronic word of mouth on purchasing decisions on e-commerce Bukalapak. The population of this study were all e-commerce consumers of Bukalapak, then the sample taken for the study was 100 respondents using the Slovin formula calculation, while the sampling used the purposive sampling method. The results of this study indicate that promotion (X1) has a positive and significant effect on purchasing decisions (Y) and service quality (X2) has a positive and significant effect on customer satisfaction (Y), while electronic word of mouth (X3) has a positive and insignificant effect on Purchase Decision (Y).